The advanced economic development process and motivating system of innovation competition - Moskalenko Oleksandra (Megatrend Revija, 2014)
The global economy destabilized by the world financial and economic crises raises the demand for the economic development model of new contents and the corresponding development strategy. This model is relevant for countries with post-transformation economies (for example, Ukraine) that by force of historical circumstances find themselves on the periphery of global economic leadership outside the effective redistribution of the results and the benefits of scientific and technological progress having lost their former technological, economic and political power. A new type of economic development should be based on an adequate theoretical model, its scientific basis and the practical verification of the ability of the country to ensure the transition to the innovatively intensive type of the economic growth. That sort of a model and its corresponding strategy focused on national peculiarities and specific of post-transformation economies is the model of the advanced economic development. The results of this study complete the theory of the economic development, promote the expansion of predictive tools and implementation of positive features of a modern economic theory, and can also be used by governments with post-transformation economies to develop the long-term strategies.